2016
DOI: 10.1556/2006.5.2016.023
|View full text |Cite
|
Sign up to set email alerts
|

The Extent and Distribution of Gambling-Related Harms and the Prevention Paradox in a British Population Survey

Abstract: ObjectivesTo examine whether the “prevention paradox” applies to British individuals in relation to gambling-related harm.MethodsData were derived from 7,756 individuals participating in the British Gambling Prevalence Survey 2010, a comprehensive interview-based survey conducted in Great Britain between November 2009 and May 2010. Gambling-related harm was assessed using an adapted version of the DSM-IV Pathological Gambling criteria. The previous year’s prevalence of problem gamblers was examined using the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 38 publications
(55 reference statements)
3
87
0
Order By: Relevance
“…This outlook acknowledges individual vulnerabilities, which may be situational as well as biological, in addition to the design and addictive potential of gambling products and environments, much of which can be influenced via the regulatory and policy environment (Livingstone & Woolley, 2007). Such an approach further acknowledges that gambling-related harm may also occur outside of the strict diagnostic criteria that define gambling disorder (Browne et al, 2016;Canale et al, 2016). It is certainly conceivable that the LDWs may lead to extended session times, or higher than intended spending in subclinical or even casual consumers of mutliline slot machines.…”
Section: Conclusioncognitive Neuroscience and Gambling Public Health mentioning
confidence: 99%
“…This outlook acknowledges individual vulnerabilities, which may be situational as well as biological, in addition to the design and addictive potential of gambling products and environments, much of which can be influenced via the regulatory and policy environment (Livingstone & Woolley, 2007). Such an approach further acknowledges that gambling-related harm may also occur outside of the strict diagnostic criteria that define gambling disorder (Browne et al, 2016;Canale et al, 2016). It is certainly conceivable that the LDWs may lead to extended session times, or higher than intended spending in subclinical or even casual consumers of mutliline slot machines.…”
Section: Conclusioncognitive Neuroscience and Gambling Public Health mentioning
confidence: 99%
“…Nonetheless, there may be several unmeasured factors that could have as much or even greater importance in shaping an individual's gambling behaviours and risk for future harm. [43]. Responsible gambling approaches that adopt a population strategy (e.g., public health campaigns that aim to correct erroneous believes about the odds of winning; promotion of safe spending limits) to reduce the average level of consumption in low to moderate risk gamblers are more likely to impact a larger portion of the population than approaches that target highly active problem gamblers (e.g., casino self-exclusion programs, pop-up messages on EGMs that only appear after an hour of continuous play).…”
Section: Limitationsmentioning
confidence: 99%
“…Eighteen studies include data on age, and several of these found that being younger was associated with a higher risk of experiencing gambling harms [40,41,42,43,33,44] . In particular one study found that younger age groups (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were at risk of dependence and social harms [45] , however some studies found younger gamblers were less at risk of financial harms [46,47] , despite one suggesting that they spent more [48] . Ferrara, Franceschini and Corsello [43] found that as well as higher rates of what they label "problematic gambling", younger age groups showed a higher comorbidity with other addictions.…”
Section: Agementioning
confidence: 99%
“…Fifteen studies examined gender, and few of these found any evidence that harms affected men and women differently [53,21,40,41] . Where differences were found these could be Health Inequality in Gambling -17 explained by other factors, such as studies that show men have a higher prevalence of harms than women [42,43,54] , being explained by men gambling more frequently than women and spending more money when gambling [45,47,55] . Raisamo et al [33] in particular found that although the prevalence of harms was higher in males, when controlling for frequency of play and amount spent gender was no longer a significant factor.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation